Objective assessment and importance of stability and motor control in sports performance - Mikolajec, K.; Rzepka, R. (Journal of Human Kinetics, 2007)
Stability is a complex process involving actions of biomechanical, motor, sensory and central nervous system (CNS) components. Fundamental goal of maintaining stability in relation to whole body is to keep center of body mass over a base of support. Number of joints systems, muscles involved, complexity of sports movements and situations requires perfect coordination of body movement patterns. In order to adapt to constantly changing situation in such dynamic environment as sports performance, optimal information input from various body sensors (visual, vestibular, somatosensory) is required. The CNS plays a crucial role in modifying input and providing optimal information to muscles to perform the best possible motor response [Hanson 1994]. Stability is often divided into two basic conditions: static and dynamic. Static stability describes the ability to maintain "static" condition when there is no significant body movement to control. Dynamic stability - essence of sport performance- is required when body moves and simultaneously is controlled for purposeful action and movement. Dynamic stability requires optimal alignment of all human body segments in order execute the best movement. In this aspect dynamic stability should be understood as not only optimal position of body in respect to base of support but also in position of particular body segments in alignment to each other. To introduce the reader into the presented subject basic terms and definitions will be presented. Postural stability by definition is described as ability.